(untitled) (The Review of Diabetic Studies, 2024)
Introduction: Evidence-Based Practice (EBP) is the universally accepted standard of providing quality, safe, and affordable healthcare services. The systematic integration is a fundamental requirement of the Saudi Commission of Health Specialties (SCFHS) and is fundamental to the realization of the national goals of the Healthcare Transformation Program by Vision 2030. Although such a strong regulatory support is in place, the published literature still reflects a gap in the policies that necessitate EBP functioning and their ongoing operationalization in Saudi Arabian clinical contexts. Study Objective: The overall goal of this systematic review is to find out and discuss the barriers and facilitators affecting the adoption and implementation of evidence-based practice (EBP) in Saudi Arabia among nurses and midwives. Methodology: The systematic review method was used and followed the PRISMA guidelines. The systematic review included the original research articles of 2013 and 2023, most of which were obtained through databases such as Scopus, Medline, and Google Scholar. The synthesis was also aimed at determining thematic patterns that were repeated in terms of time, resources, leadership support, knowledge gaps, and organizational culture impact on professional practice and autonomy. Conclusion: The review validates that structural and organizational barriers are the main barriers to the adoption of EBP. The lack of resources and organizational support, as well as the inadequacy of time and excessive workloads are the most perilous obstacles that are mentioned by the practitioners. The presence of these resource constraints is greatly enhanced by a hierarchical organizational culture where professional autonomy is discouraged, the spirit of inquiry is suppressed and evidence-based change to the routine practice is hindered. Although there are individual gaps in knowledge (mostly in critical appraisal skills) most gaps are dependent on structural support to achieve successful implementation.